Effect of Transcranial Direct Current Stimulation on Professional Female Soccer Players' Recovery Following Official Matches. Issue 4 (August 2021) - Moreira, Alexandre; Machado, Daniel Gomes da Silva; Bikson, Marom; Unal, Gozde; Bradley, Paul S.; Moscaleski, Luciane; Costa, Taline; Kalil, Gabriella C .S. G.; Chao, Liaw W.; Baptista, Abrahão F.; Morya, Edgard; Okano, Alexandre H.
This study investigated the effect of transcranial direct current stimulation (tDCS) combined with a recovery training session on the well-being and self-perceived recovery of professional female soccer players after official matches. Data from 13 world-class players were analyzed after participating in four official soccer matches of the first division of the Brazilian Women's Soccer Championship (7-, 10-, and 13-day intervals). We applied anodal tDCS (a-tDCS) over the left dorsolateral prefrontal cortex with 2 mA for 20 minutes (+F3/−F4 montage) the day after each match. Participants underwent two randomly ordered sessions of a-tDCS or sham. Players completed the Well-Being Questionnaire (WBQ) and the Total Quality Recovery (TQR) scale before each experimental condition and again the following morning. A two-way repeated-measures ANOVA showed a significant time x condition interaction on the WBQ (F(1, 11) =5.21; p =0.043; ηp 2 =0.32), but not on the TQR (F(1, 12)  = 0.552; p =  0.47; ηp 2  = 0.044). There was a large effect size (ES) for a-tDCS for the WBQ score (ES = 1.02; 95%CI = 0.17;1.88), and there was a moderate WBQ score increase (ES = 0.53; 95%CI = −0.29;1.34) for the sham condition. We found similar increases in the TQR score for a-tDCS (ES = 1.50; 95%CI = 0.63–2.37) and the sham condition (ES = 1.36; 95%CI = 0.51–2.22). These results suggest that a-tDCS (+F3/−F4 montage) combined with a recovery training session may slightly improve perceived well-being beyond the level of improvement after only the recovery training session among world-class female soccer players. Prior to widely adopting this recovery approach, further study is needed with larger and more diverse samples, including for female teams of different performance levels.